Experimental ingestion of fluorescent microplastics by pacific oysters, Crassostrea gigas, and their effects on the behaviour and development at early stages. (September 2020) - Bringer, Arno; Cachot, Jérôme; Prunier, Grégoire; Dubillot, Emmanuel; Clérandeau, Christelle; Hélène Thomas,
Abstract: Plastics are persistent synthetic polymers that accumulate as waste in the marine environment. Microplastics (MPs, <5 mm) can be found either as microbeads in body care and some industrial products or as plastic debris through degradation. Plastic microbeads (1–5 μm, fluorescent, Cospheric) were used to characterise the MP ingestion and determine their potential harmful effects on both the swimming behaviour and development of oyster D-larvae ( Crassostrea gigas ). For 24 h, embryos were first exposed to MPs at a temperature of 24 °C. In addition, 3 day-old D-larvae were exposed to the same temperature for 1, 3 and 5 h. Three concentrations of MPs were used: 0.1, 1 and 10 mg MP. L −1 . After a 24-h period of embryonic exposure, we noted that MP agglomerates were stuck to the D-larvae coat and locomotor eyelashes. We also observed a significant increase in severe malformations and developmental arrests for larvae exposed to MPs ranging from 1 mg MP. L −1 . In terms of swimming behaviour, the maximum speed recorded was lower for larvae exposed at 0.1 and 1 mg MP. L −1 . After an acute exposure to MPs, particles were found in the digestive tract of 3 dpf (days post fertilisation) D-larvae. After 1-h exposure, the concentrations tested (0.1, 1 and 10 mg MP. L −1 ) resulted in respectively 38%, 86% and 98%. The larvae swimming behaviour was recorded and analysed. Unlike the results observed at the embryo-larval stage, 3-dpf larvae showed significant impacts with no dose-response effect. Graphical abstract: Image 1 Highlights: Different development stages exposure to fluorescent microplastics (MPs) 1–5 μm. MPs affected swimming activity and development for 24 h oyster D-larvae. Presence of MPs on oyster D-larvae eyelashes and coat. Presence of MPs in digestive tract for 72 h oyster D-larvae. No MPs effects on swimming activity for 72 h oyster D-larvae.